UNDERSTANDING THE ROLE OF VALUES IN LATIN AMERICAN HEALTH SYSTEMS - Velez, Claudia Marcela (My University, 2019)
It is often not clear how values are incorporated into policy decision-making about health systems. This is perhaps not surprising given the complexity of decision-making about health systems, the wide range of values prioritized (and advocated for) by different stakeholders, the broad array of sources for or mechanisms available to identify values, and the many ways in which values can drive policy decisions, as well as the reality that policymakers often do not want to be explicit about the values used in policy decision-making process. Using synthesis and qualitative research methods, this dissertation investigates the role of values in policy decision-making about health system financing in Latin America and contributes to the understanding of this field by providing insights for policy and research. The dissertation moves from a general and descriptive focus to a specific and explanatory focus. First, a critical interpretive synthesis was used to develop a theoretical framework that identifies how and under what conditions values inform policy decision-making about health system financing in Latin American countries. In chapters 3 and 4, the focus narrows by using an embedded multiple-case study design that analyzes two specific decisions in each of Chile and Colombia. Frameworks that explain government agenda setting and policy development and the theoretical framework developed in chapter 2, are used to analyze these decisions. The second study (chapter 3) is a discourse analysis which qualitatively assess how declared values inform the four decisions in Chile and Colombia. The third study (chapter 4), draws on in-depth qualitative interviews to understand how and why policymakers and stakeholders use declared and undeclared values in those four decisions in Chile and Colombia. The research chapters build on each other and make substantive, methodological and theoretical contributions. The dissertation provides a rich understanding of the roles of values in health system financing decisions through a critical interpretive synthesis and two qualitative studies, adding to the evidence base that stakeholders and policymakers can draw from when making or shaping policy decisions. These studies collectively build an understanding about what values inform the health policy process in Latin America, how those values work, under what conditions they come to be influential, how they are applied in real decisions, and why policymakers and stakeholders perceive that values play a role in real decisions. All of this evidence has contributed to the development a new theoretical framework about the roles of values in health systems.
THE ROLES OF VALUES IN HEALTH SYSTEMS
Keywords: values, health system financing, policy decision-making, Latin American Countries, LMIC, Chile, Colombia, AUGE plan, Ricarte Soto, T-760, Ley estatutaria, CIS, discourse analysis, case study